Orbital melanoma masquerading as a "Galloping haemangioma". (4th March 2017) - Lorenzano, Daniele; Miszkiel, Katherine; Rose, Geoffrey E.
ABSTRACT: We describe a 32-year-old pregnant woman who was referred to our clinic after 6 weeks of observation elsewhere with a rapidly expanding orbital mass, proptosed globe and slowly decreasing of vision in her left eye. To our examination the patient presented with congested optic disc fine macular striae and some slight choroidal elevation without any retinal pigmentation. An MRI scan without contrast was performed, suggesting the signal charactheristics of an orbital mass consistent with a cellular lesion such as a cavernous hemangioma or a solitary fibrous tumour. Despite the benign-looking imaging, the fast-growing pattern of the lesion suggested a more sinister picture. A fine needle aspiration of the orbital mass was carried out, revealing the presence of an amelanotic melanoma. This case highlights the importance of considering the presence of a melanoma when there is a clear history of a rapid lesion progression.